Lessons Learned during a Rapidly Evolving COVID-19 Pandemic: Aboriginal and Torres Strait Islander-Led Mental Health and Wellbeing Responses Are Key - Patricia Dudgeon; Jemma R. Collova; Kate Derry; Stewart Sutherland (International Journal of Environmental Research and Public Health, 2023)
As the world journeys towards the endemic phase that follows a pandemic, public health authorities are reviewing the efficacy of COVID-19 pandemic responses. The responses by Aboriginal and Torres Strait Islander communities in Australia have been heralded across the globe as an exemplary demonstration of how self-determination can achieve optimal health outcomes for Indigenous peoples. Despite this success, the impacts of pandemic stressors and public health responses on immediate and long-term mental health and wellbeing require examination. In December 2021, Aboriginal and Torres Strait Islander mental health and wellbeing leaders and allies (N = 50) attended a virtual roundtable to determine the key issues facing Aboriginal and Torres Strait Islander peoples and communities, and the actions required to address these issues. Roundtable attendees critically reviewed how the rapidly evolving pandemic context has impacted Aboriginal and Torres Strait Islander mental health and social and emotional wellbeing (SEWB). This paper presents an overview of this national collaborative consultation process, and a summary of the key issues and actions identified. These results build on evidence from other roundtables held in Australia during 2020, and the emerging consensus across the globe that Indigenous self-determination remains essential to Indigenous SEWB, especially during and following a pandemic.